SISTEM INFORMASI GEOGRAFIS (Geographic Informational System) A Local Road Mapping and Second Collector in South Jakarta Using OpenGeo Suite and PostgreSQL - Chairunnas, Andi; Yusuf, Daud (Proceedings of KNASTIK, 2012)
Jakarta is Indonesian’s capital city which is the central of the most activity andeconomical activity for the people from all around Indonesia. The High mobility ofroad user is one of the things that become a problem in Jakarta. A road is a primaryaspect for a good traffic. The road itself is depend on how good or how bad thecondition itself, such as the construction, aging and a weight of the vehicle and There isa possibility of the quality of road is going to change depend on the situation.A road mapping is needed to deciding, planning and to caring the road by thegovernment to build a good traffic of people’s transportation. That is why, the localroad mapping is very important. The present writer is making a Sistem InformasiGeografis (Geographic informational system-SIG) which is talking about local roadmapping and a second collector which is using an OpenGeo Suite with the support fromframework OpenLayers. OpenGeo Suite is used for mapping digitalization process.PostgreSQL 8.2.4. Is used as a data base and Adobe Dreamweaver CS 3 is used to editthe PHP coding system. The mapping system from the layer is contains of roaddimension, technique of the road, road location, road condition and road user. By theSIG local road mapping site and second collector, people is be able to know about theroad mapping easily and it also be able to be the key for a planning and caring of theroad in the south Jakarta.